Applicability of the Environmental Relative Moldiness Index for Quantification of Residential Mold Contamination in an Air Pollution Health Effects Study. (6th November 2014) - Kamal, Ali; Burke, Janet; Vesper, Stephen; Batterman, Stuart; Vette, Alan; Godwin, Christopher; Chavez-Camarena, Marina; Norris, Gary
Abstract : The Near-Road Exposures and Effects of Urban Air Pollutants Study (NEXUS) investigated the impact of exposure to traffic-related air pollution on the respiratory health of asthmatic children in Detroit, Michigan. Since indoor mold exposure may also contribute to asthma, floor dust samples were collected in participants homes (n = 112 ) to assess mold contamination using the Environmental Relative Moldiness Index (ERMI). The repeatability of the ERMI over time, as well as ERMI differences between rooms and dust collection methods, was evaluated for insights into the application of the ERMI metric. ERMI values for the standard settled floor dust samples had a mean± standard deviation of14.5 ± 7.9, indicating high levels of mold contamination. ERMI values for samples collected from the same home 1 to 7 months apart (n = 52 ) were consistent and without systematic bias. ERMI values for separate bedroom and living room samples were highly correlated (r = 0.69, n = 66 ). Vacuum bag dust ERMI values were lower than for floor dust but correlated (r = 0.58, n = 28 ). These results support the use of the ERMI to evaluate residential mold exposure as a confounder in air pollution health effects studies.